(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2021)
This study aims to determine whether the dimensions ESQ in service quality, namely reliability, responsiveness, access, flexibility, ease of navigation, efficiency, assurance, security, science price, aesthetic situ, and personalization affect the user satisfaction Department of Labor Cooperatives and Small medium Kebumen. The population in this study is the service users Department of Labor Cooperatives, Small and Medium Kebumen. The sample of 100 respondents by using the technique of Non-Probability Sampling with accidental sampling approach, ie sampling technique based on chance, ie who happened to meet the researchers can be sampled if deemed suitable. Based on statistical data analysis, indicators in this study is valid and the variables are reliable. The sequence individually on each of the most influential variable is the variable responsiveness with a regression coefficient of 0.257, and knowledge of the price of the regression coefficient of 0.157, followed by a guarantee by the regression coefficient of 0.120, the security of the regression coefficient of 0.120, while the variables that influence the lowest was efficient with a regression coefficient of 0.069. Department of Labor and Cooperatives, Small and Medium Enterprises Kebumen need to retain the elements that have been rated by consumers as well as the need to fix the things that are lacking.